Leukospermia in Infertile Men and Successful Intrauterine Insemination at Rumah Sakit Ibu dan Anak Puri Bunda Denpasar - I Gusti Ngurah Pramesemara; Yukhi Kurniawan; Anak Agung Ngurah Perdana Anantadiva; I Gusti Ayu Widianti (Indonesian Andrology and Biomedical Journal, 2023)
Infertility is a condition after a year of regular sexual intercourse, without the use of contraceptives, and ends with the absence of pregnancy. Intrauterine Insemination (IUI) is a procedure that is widely used in fertility clinics and is usually the first treatment option in patients who are experiencing infertility disorders, diagnosis of infertility due to cervical factors, diagnosis of factor infertility in men, and diagnosis of unexplained infertility. the cause. IUI is also a simple, inexpensive, and quite effective infertility treatment. One of the factors that can influence the success of IUI is leukospermia. This study is an analytical study using a cross-sectional design and using medical records of patients diagnosed with infertility, aged from 25 to 45 years, and undergoing IUI procedures from January to June 2022 at the RSIA Puri Bunda Denpasar. The sampling method in this study used a purposive sampling method which was selected based on inclusion and exclusion criteria. In this study, 53 samples were obtained. Of the 53 samples that have been collected, 13 people experienced leukospermia (24.5%), 40 people were non-leukospermic (75.5%). The success of IUI in this study was 17 people (32.1%) consisting of 3 leukospermic (23.1%) and 14 non-leukospermic (35.0%). The results of the Fisher's Exact test obtained, namely the p value = 0.511, it can be concluded that leukospermia with the success of IUI does not have a significant relationship. Calculation of odds ratio (OR) obtained a figure of 1.759 (CI95% 0,423-7,610).